Practical exploitation of mycorrhizal fungi in agricultural systems - Brito, Isabel (2014)
Improving the sustainability of agricultural systems requires a more efficacious use of soil resources. Mycorrhizas are known to contribute to host plant P acquisition and protection against both biotic and abiotic stresses, such as soil-borne diseases and toxic metal ions. However, practical exploitation of the mutualistic relationship is rarely considered in agricultural systems, allegedly owing to the cost of inoculation and the requirement for timely colonisation. To overcome these limitations, the presence of an extensive extraradical mycelium (ERM) from indigenous arbuscular mycorrhizal fungi (AMF) could be used as the preferential source for colonisation of a crop plant. Colonisation of crop roots starting from an intact ERM takes place faster and generally forms a more effective mycorrhizal association than when initiated from other propagules such as spores and root fragments. We report on the ability of an intact ERM developed by indigenous AMF population on mycotrophic plants (Developers) to significantly improve the AMF colonisation of wheat, subterranean clover and maize allowing for a better performance of the crop. This mechanism allowed the protection of wheat and subterranean clover from excessive Mn concentration in the shoots or in the roots, as in the case of the clover, leading to a greater growth of the crop (2.7 and 4.7 times respectively). Using the same strategy to promote the AMF colonisation of maize, the crop was able to exhibit high levels of colonization, even up to 45 kg P.ha-1 of applied P, and the plants took advantage in terms of P use efficiency. Our results indicate that the use of intact ERM as preferential AMF propagule is a valid strategy to increase the role of this symbiosis under marginal or more intensive cropping systems, through simple adaptations to both crop rotations and tillage practices.